Technical aspects of composite arterial T-grafts: Estimation of required conduit length by a simple formula - Albert, A.; Hassanein, W.; Florath, Ines; Voehringer, L.; Abugameh, A.; Ennker, J. (2008)
Background: When composite arterial T-grafts are used, uncertainty persists as to whether the RIMA will be long enough to reach the RCA. We present a formula for the preoperative estimation of the required conduit length. Methods: The following formula was created to estimate the required conduit length for a sequential graft, starting from the proximal RIMA-LIMA T-graft anastomosis, passing the PLA, and ending at the PDA: 2.14 × ([2 × LV wall thickness [WT])+ end-diastolic diameter (EDD)]. The estimated length was compared to the measured length in 100 patients undergoing off-pump revascularisation with BIMA T-grafts. Results: There were no hospital deaths, no major infarctions and no wound complications. The required conduit length varied from 11.5 cm to 19 cm (average 14.9 ± 1.4 cm) and was excellently predicted by the formula (paired t-test: p < 0.001, r=0.86, average overestimation: 0.55 cm). Conclusion: The formula reliably determines the minimum required conduit length. We recommend this formula for preoperative decision making when considering the choice of graft and the length of RIMA harvesting. To facilitate calculation a simplified version is useful: 2 × EDD + 4 × WD + 1. Avoiding uncertainty about the sufficiency of the RIMA length may contribute to the spread of this technique. © Georg Thieme Verlag KG Stuttgart.